Hubungan Asupan Zat Gizi Dan Status Gizi Terhadap Kejadian Menstruasi Dini Pada Siswi SMPN 1 Kabaena Timur - Hariani Hariani; Deris Atma Subrin (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
Early menstruation in adolescents can be influenced by nutritional status and nutrients consumed by teenagers. This studyaims to determine the relationship of nutrient intake and nutritional status on the incidence of early menstruation at SMPN 1East Kabaena. This research is descriptive analytic with Cross Sectional Study. The population in this study were allstudents of SMPN 1 East Kabaena as many as 94 people. Sampling technique was purposive sampling. Data were obtainedusing a questionnaire and anthropometric measurements. Data were analyzed by using Chi-square test. Results show thatfrom 42 adolescents who consumed enough energy, there were 25 people (59.5%) experienced early menstruation, andfrom 38 adolescents who consumed less protein, there were 29 people (76.3%) experienced early menstruation. While the33 adolescents who consumed less fat, there were 25 people (75.8%) experienced early menstruation, and of 37 teenagerswho consumed more carbohydrates, there were 24 people (64.9%) had normal menstruation, while from 37 teenagers whohad over-nutrition status, there were 24 people (60.0%) had normal menstruation. The results show that there is arelationship between nutritional intake and nutritional status with the incidence of early menstruation in female students atSMPN 1 East Kabaena.